according to your approach for second problem i ended up with an equation

like this

how can i move further towards the answer?

like this

how can i move further towards the answer?

The Gateway to Computer Science Excellence

0 votes

Solve the following recursions ( in terms of Θ ).

T(0) = T(1) = Θ(1) in all of the following.

- $T(n) = n + \frac{1}{n}\sum_{i=0}^{i=n-1}T(i)$
- $T(n) = n + \frac{2}{n}\sum_{i=0}^{i=n-1}T(i)$
- $T(n) = n + \frac{4}{n}\sum_{i=0}^{i=n/2}T(i)$
- $T(n) = n + \frac{40}{n}\sum_{i=0}^{i=n/5}T(i)$

52,315 questions

60,433 answers

201,778 comments

95,257 users